1987
DOI: 10.1192/bjp.150.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Auditory P3 Event-related Potential in Schizophrenia and Depression

Abstract: Event-related potentials during a two-tone discrimination task were recorded in 24 schizophrenic patients, 16 depressed patients and 59 control subjects. Recordings were made when patients were medication-free. Fourteen schizophrenic and 13 depressed patients were retested at 1 and 4 weeks after the start of treatment, and 13 schizophrenic patients were also tested between 6 and 24 months after the initial recordings. In the schizophrenic group, the P3 latency was significantly prolonged compared with that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
1
4

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(144 citation statements)
references
References 17 publications
(7 reference statements)
9
130
1
4
Order By: Relevance
“…The present investigation was performed in order to replicate the findings concerning different functional mechanisms underlying the reduced P300 in depressives and schizophrenics (Röschke et al, 1996c), which has been reported for the averaged signals in previous studies (Roth et al, 1980a(Roth et al, , b, 1981Brecher and Begleiter, 1983;Pfefferbaum et al, 1984;Diner et al, 1985;Blackwood et al, 1987;Gandaghar et al, 1993). In a former study, we reported the replication of a reduced number of 'true positive' P300 waves in schizophrenics (Wagner et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present investigation was performed in order to replicate the findings concerning different functional mechanisms underlying the reduced P300 in depressives and schizophrenics (Röschke et al, 1996c), which has been reported for the averaged signals in previous studies (Roth et al, 1980a(Roth et al, , b, 1981Brecher and Begleiter, 1983;Pfefferbaum et al, 1984;Diner et al, 1985;Blackwood et al, 1987;Gandaghar et al, 1993). In a former study, we reported the replication of a reduced number of 'true positive' P300 waves in schizophrenics (Wagner et al, 2000).…”
Section: Discussionsupporting
confidence: 74%
“…Especially for schizophrenics this could be confirmed in several investigations (Roth et al, 1980a, b;Brecher and Begleiter, 1983;Pfefferbaum et al, 1984;Ford et al, 1994). For depressives, the majority of studies also report a reduced P300 amplitude (Roth et al, 1981;Pfefferbaum et al, 1984;Diner et al, 1985;Blackwood et al, 1987;Gandaghar et al, 1993).…”
Section: Introductionmentioning
confidence: 69%
“…Averaging of the correct and artefact-free EEG-epochs typically reveals significantly higher P300 amplitudes at parietal electrode leads for the rare target as compared to the frequent distractor tones, which is commonly interpreted as an indication of stronger neuronal activity in the target condition. This P300 component has been repeatedly shown to have reduced amplitudes and prolonged latencies in patients with depressive disorders as compared to healthy age-and gender-matched controls (Roth et al 1981;Pfefferbaum et al 1984;Blackwood et al 1987;Urretavizcaya et al 2003;Kawasaki et al 2004). Although altered P300 amplitudes and latencies are reported quite robustly across studies, the problem of these measures is their low specificity.…”
Section: Neurophysiological Findingsmentioning
confidence: 97%
“…Anticholinergic medi cation, which according to some authors may be related to increased P3 latencies, was not involved in our study, and our use of the expression â€oe¿ mono therapy― excluded all kinds of psychoactive drugs with the exception of haloperidol. Neuroleptic drugs themselves, at least at the commonly used dosages, probably do not affect P3 latency (Blackwood et a!, 1987). Pfefferbaum et a!…”
Section: Sir: We Agree With Dr Ebmeier and Colleagues Thatmentioning
confidence: 99%